A comparative study of different heat exchange systems in a thermoelectric refrigerator and their influence on the efficiency. (25th June 2016) - Astrain, D.; Aranguren, P.; Martínez, A.; Rodríguez, A.; Pérez, M.G.
Highlights: Total efficiency optimisation of a thermoelectric refrigerator. Experimental study of three different types of heat exchangers for thermoelectrics. Influence of the occupancy ratio in thermal resistance. Important decrease in the electric consumption of a thermoelectric refrigerator. Abstract: Thermoelectric refrigeration (TEC) exhibits several advantages compared to vapour-compression, since this technology presents accurate temperature control systems and higher levels of compactness, robustness and noiselessness. However, its low efficiency is acting as a deterrent for it to spread in the refrigeration market. One of the factors determining the efficiency of a thermoelectric refrigerator is the temperature difference between the hot and cold sides of the thermoelectric modules (TEMs). This is dependent on the thermal resistances of the heat exchangers used. This paper discusses the results of an experimental study of different types of heat exchangers for the thermoelectric module hot side: a water–air system comprising a cold plate, pump and fan coil; a finned heat sink with fan; a heat pipe with fan. Expressions of thermal resistance have been obtained for these three types as a function of the air and water mass flows and the number of TEMs per unit of surface area of heat exchanger (occupancy ratio, δ ), as well as expressions of the power consumed by the fans and the pump. Finally, a computational study has been carried out on a thermoelectric refrigerator of 15 m 3 of interior volume, in order to obtain the influence of the heat exchanger studied, on the total consumption of the refrigerator and its efficiency. The results have demonstrated that relevant improvements can be made in TEC efficiency by the proper optimisation of the heat exchangers.